The Implementation of 3-N (Niteni, Nirokke, Nambahi) Teaching Strategies Concept to Improve Students’ Speaking Skill - Asnawi Muslem; Nur Mulia Nanda; Nira Erdiana (FKIP Universitas Lampung, 2024)
The Implementation of 3-N (Niteni, Nirokke, Nambahi) Teaching Strategies Concept to Improve Students’ Speaking Skill. Objectives: This study is intended to determine if using the 3-N teaching strategies significantly improves students’ speaking skills. Methods: A pre-experimental design is used to collect data from the same group of participants before and after the implementation of an intervention. This design is often used to evaluate the effectiveness of an intervention over a limited time. A pre-experimental design makes it necessary to collect data from participants before administering the intervention, administer the intervention, and collect data after the intervention to observe changes and effects. The researcher conducted treatment for students, the treatment was performed five times, including the pre-test and post-test. Findings: The treatment succeeded in improving students’, both with low and high initial understanding. The use of the 3-N teaching concept is effective in improving students’ speaking skills, especially in the vocabulary aspect. Conclusion: The use of 3-N provides benefits to students, they can get the opportunity to listen and imitate before they create their work. It can also add to the student’s creativity because they can also modify and add to what they have learned. Keywords: niteni, nirokke, nambahi, vocabulary, speaking skill.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202454